2004
DOI: 10.1590/s1519-566x2004000200013
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade e tamanho de himenópteros parasitóides de Brevicoryne brassicae L. e Aphis nerii Boyer de Fonscolombe (Hemiptera: Aphididae)

Abstract: -The objective of this work was to record the diversity of parasitoid of two aphid species, Brevicoryne brassicae L. and Aphis nerii Boyer de Fonscolombe in a site at Uberlândia, MG, and the relationship between parasitoid size and their mummies size, with reference to the host species. B. brassicae were collected on kale (Brassica oleracea L. var. acephala D.C.) and A nerii on milkweed (Asclepias curassavica L.). Samplings were made monthly from May, 1999 to May, 2000 in two experimental gardens. Morphometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
3
15
0
7
Order By: Relevance
“…Our results differ from those of Elliott et al (1994), who observed that 25% of the larvae of A. colemani in B. brassicae reached the mummy stage and 5% reached the adult stage, indicating a low host quality. Although there are some reports of A. colemani parasitizing B. brassicae in the field, it is always at a low level (Vaz et al, 2004;Starý et al, 2007), which also indicates that B. brassicae is not a good host for A. colemani.…”
Section: Discussionmentioning
confidence: 94%
“…Our results differ from those of Elliott et al (1994), who observed that 25% of the larvae of A. colemani in B. brassicae reached the mummy stage and 5% reached the adult stage, indicating a low host quality. Although there are some reports of A. colemani parasitizing B. brassicae in the field, it is always at a low level (Vaz et al, 2004;Starý et al, 2007), which also indicates that B. brassicae is not a good host for A. colemani.…”
Section: Discussionmentioning
confidence: 94%
“…PALAVRAS-CHAVE: Insecta, interação hospedeiro-parasitóide, interação presa-predador, interação .....formiga-homóptero, olericultura orgânica Os afídeos ou pulgões, particularmente Brevicoryne brassicae L. (Hemiptera: Aphididae) e Myzus persicae (Sulzer) (Hemiptera: Aphididae), são pragas bastante freqüentes e causam apreciáveis danos às brassicáceas, como couve, brócolis, nabo, couve-flor, repolho e mostarda (SousaSilva & Ilharco 1995, Blackman & Eastop 2000. Tais insetos são geralmente atacados por uma variedade de insetos predadores e parasitóides (Minks & Harrewijn 1988, Emden & Wratten 1990, Vaz et al 2004. Todavia, a diversidade da fauna de predadores e parasitóides de uma determinada espécie de pulgão pode ser influenciada pela co-ocorrência de outras espécies de presas e hospedeiros potenciais (Vaz et al 2004).…”
unclassified
“…Tais insetos são geralmente atacados por uma variedade de insetos predadores e parasitóides (Minks & Harrewijn 1988, Emden & Wratten 1990, Vaz et al 2004. Todavia, a diversidade da fauna de predadores e parasitóides de uma determinada espécie de pulgão pode ser influenciada pela co-ocorrência de outras espécies de presas e hospedeiros potenciais (Vaz et al 2004). Por outro lado, as formigas simbiontes de pulgões podem protegê-los desses agentes de mortalidade, ao se alimentarem de seus excrementos ricos em açúcar, reduzindo as taxas de parasitismo e/ou predação dos pulgões, o que por sua vez, pode resultar em aumento das taxas de reprodução e sobrevivência dos homópteros (Takada & Hashimoto 1985, Buckley 1987.…”
unclassified
“…Cosmopolitan (Ferrer-Suay et al 2012a). Argentina (de Santis 1937;Pujade-Villar et al 2002;Berta et al 2002), Brazil (Betini 1975;Betini 1976;Lazzari 1985;Tavares 1991;Cividanes 2002;Pujade-Villar et al 2002;Vaz et al 2004 …”
Section: Alloxysta Fuscicornis (Hartig 1841)mentioning
confidence: 99%